2015
DOI: 10.1007/s12035-015-9220-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Levels of Neopterin at Admission Predicts Depression After Acute Ischemic Stroke: a 6-Month Follow-Up Study

Abstract: Inflammation and cell-mediated immune activation are attributed to the pathogenesis and pathophysiology in depression. Our aim was to test the possible association between serum levels of neopterin and the development of post-stroke depression (PSD) in Chinese patients. The subjects were first-ever acute ischemic stroke patients who were hospitalized at the First Affiliated Hospital of Xinxiang Medical University during the period from December 2012 to December 2013. Clinical information and stroke severity we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Urinary neopterin levels in depressed patients have also been reported to be significantly higher as compared to healthy controls [163, 164]. Similar finding was reported by a more recent study [165], which also indicated that 6-months after an acute ischemic stroke, neopterin could be an independent predictor for the development of major depression. Interestingly, serum neopterin levels were reported to be significantly higher before treatment in anti-psychotic naive schizophrenia-patients, as compared to healthy controls, which reportedly declined significantly after 3 months of treatment with anti-psychotic medications [166].…”
Section: Inflammation As a Common Denominatorsupporting
confidence: 71%
“…Urinary neopterin levels in depressed patients have also been reported to be significantly higher as compared to healthy controls [163, 164]. Similar finding was reported by a more recent study [165], which also indicated that 6-months after an acute ischemic stroke, neopterin could be an independent predictor for the development of major depression. Interestingly, serum neopterin levels were reported to be significantly higher before treatment in anti-psychotic naive schizophrenia-patients, as compared to healthy controls, which reportedly declined significantly after 3 months of treatment with anti-psychotic medications [166].…”
Section: Inflammation As a Common Denominatorsupporting
confidence: 71%
“…Unfortunately, the poor quality of the studies done to date do not allow for a definitive connection between PSD and inflammation to be made. In some studies, early markers of inflammation like CRP [57], ferritin [58], and neopterin [59] were associated with the later development of PSD. High serum levels of leptin at days 7 and 30 after stroke have also shown an association with later development of PSD [60].…”
Section: Inflammation and The Biological Basis Of Psdmentioning
confidence: 99%
“…One of the inflammatory drivers of this diversion of 5-HT to KYN is neopterin, a catabolic product of guanosine triphosphate that is a marker of cellular immune system activation produced by macrophages upon stimulation by interferon-gamma. 2528 Increased peripheral KYN results in increased central KYN. KYN is further broken down into quinolinic acid, which potently agonizes the N-methyl-D-aspartate (NMDA)-receptor causing excitotoxic effects through receptor over-activation 29, 30 and inhibits glutamate uptake that causes elevated extracellular glutamate concentrations.…”
Section: Introductionmentioning
confidence: 99%